Integration of local wisdom of natural color sasirangan in project-based learning with steam approach to train science literacy - Fuad, Zainal; Sholahuddin, Arif; Mahardika, Andi Ichsan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Science learning should provide meaningful experiences for students to understand various scientific phenomena in life. Integrating local wisdom in learning can improve scientific literacy because the various concepts learned are witnessed directly by students in life. This research aim of developing science LKPD integrated with local wisdom of sasirangan natural colors to improve project-based science literacy with the STEAM approach. The research approach used is qualitative research. Based on the research results and discussion, it can be concluded that the project-based learning model is very appropriate to be applied with the STEAM approach so that learning activities are student-centered, create meaningful learning, and train science literacy. Based on these findings, teachers should design media and lesson plans that are integrated with local wisdom and apply them in classroom learning.